Development of Alternative and Augmentative Communication Media System for Autism Spectrum Disorder with Complex Communication Needs - Rezkiani, Kiki; Aprilia, Imas Diana (Angstrom Centre of Education, 2023)
This study aims to help children with autism spectrum disorder (ASD) with difficulties communicating, especially expressive language. This research develops alternative and augmentative communication media needed in expressing his wishes to the people around him in everyday life. This study uses a research and development (R&D) model with a qualitative descriptive approach to explaining alternative and augmentative communication media use. This research results in an alternative and augmentative communication media called